eLearning in the USA: The Standard? The Benchmark? - Rolf Schulmeister (FernUniversität Hagen, 2007)
More than 3 million enrolments in online courses in the USA are reported by American sources. The essay investigates the role of online studies within the American educational system and tries to find out more about the exact meaning of these extremely high figures. The research discovers astonishing facts and relations: Public schools offer more online courses (82%) than private schools, and 52% of all online courses are offered by 2-year colleges for the associate degrees (and only 8% for the bachelor). A majority of online courses fulfill the role as "remedial courses" that serve for "credit recovery" (U.S. department of Education).The quality of these courses is not very high. This applies to the use of media as well as to the didactic concept. The teaching staff mainly consists of hired part-time lecturers who are still at the very entrance level to an academic career.The essay wants to initiate a discussion about the question if the European study system is in danger to imitate the shortcomings and consequences of the American educational system, because the European system is approximating the American due to recent political decisions. Can we still pursue the aims that we proclaimed when starting with eLearning, if in future eLearning will have to be used to repair the consequences of the bachelor?